2014
DOI: 10.1016/j.jalz.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and health‐related risk factors and risk of cognitive aging among older veterans

Abstract: Lifestyle and health-related factors are critical components of the risk for cognitive aging among veterans. Because dementia has a prolonged prodromal phase, understanding effects across the life course could help focus the timing and duration of prevention targets. This perspective may be especially relevant for veterans and health behaviors. Military service may promote development and maintenance of healthy lifestyle behaviors, but the period directly after active duty has ended could be an important trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 144 publications
3
43
0
3
Order By: Relevance
“…Age- related differences in flow rate limited to a subgroup that was genetically predisposed to lesser synaptic dopamine availability. In contrast to stable and immutable genetic variations, vascular risk factors examined here can be modified and mitigated via life-style changes and pharmaceutical interventions (Yaffe et al 2014). Thus, if indeed the differences in blood flow rate are linked to declines in cognitive performance, addressing such modifiable factors can be a valuable contribution to ameliorating the course of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Age- related differences in flow rate limited to a subgroup that was genetically predisposed to lesser synaptic dopamine availability. In contrast to stable and immutable genetic variations, vascular risk factors examined here can be modified and mitigated via life-style changes and pharmaceutical interventions (Yaffe et al 2014). Thus, if indeed the differences in blood flow rate are linked to declines in cognitive performance, addressing such modifiable factors can be a valuable contribution to ameliorating the course of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, lifestyle involves regular daily activities, and people's health status is directly affected by such activities. A health promoting lifestyle includes behaviors, such as healthy diet, adequate physical activity, health care responsibility, stress management, good interpersonal relationship, and spiritual development (13). Health behavior studies in 35 different countries as a project by the World Health Organization (WHO) indicated that lifestyle and behaviors have about a 60% share in human health and QOL (11).…”
Section: Introductionmentioning
confidence: 99%
“…Health promotion empowers people to obtain greater control over their behaviors (14). It should be noted that several studies concentrated on promoting lifestyle and quality of life in veterans with PTSD (7,13,(15)(16)(17), whereas very few studies have considered people related to these veterans, especially their spouses (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Unhealthy lifestyle behaviours are also associated with reduced cognitive function in elderly individuals (Lee et al, 2014). In particular, recent studies have reported that lifestyle-related factors (ie, physical activity, nutrition, quality of sleep, smoking, and alcohol consumption) are important risk factors for poor aging cognitive function (Yaffe, Hoang, Byers, Barnes, & Friedl, 2014).…”
mentioning
confidence: 99%